A New Approach for Road‐Vehicle Vibration Simulation. Issue 5 (23rd May 2017) - Zhou, Hao; Wang, Zhi‐Wei
Abstract : A new approach for road‐vehicle vibration simulation is proposed and demonstrated feasible by testing with three express‐road vehicle‐vibration records, that is, record A, two‐wheel electric bicycle, 80% loaded, traveling on urban road; record B, median van, 50% loaded, traveling on urban road; and record C, minivan, 80% loaded, traveling on urban road too. This method decomposes the original signal into a series of approximate Gaussian‐vibration segments and a shock segment with high kurtosis by moving crest factor and one‐tenth peak‐value method. Simulate Gaussian‐distribution vibration one by one from the power spectral density (PSD) of each decomposed segments. The overall signal is simulated by concatenating of each decomposed Gaussian segment. The simulated signal has not only the same overall root‐mean‐square (RMS), duration as the original signal, but also has a similar PSD to the original signal, without incurring excessive acceleration levels. This allows an improved and more representative simulated input signal to be generated that can be use in the current generation of vibration table. Abstract : The vehicle vibration signal can be decomposed into a series of approximate Gaussian distribution vibration segments and a shock events segments. And each segment can be simulated by a Gaussian vibration signal, concatenating these Gaussian vibration segments to obtain the overall simulated signal. The simulated signal not only has the same overall RMS, duration as the original signal, but also has a similar PSD to the original signal.